2021
DOI: 10.1186/s12889-021-10602-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of accommodation environments in student mental health and wellbeing

Abstract: Background Due to the increasing concern over student mental health and wellbeing, attention has turned to the matter of creating environments, communities, and institutions which enable students to flourish. Methods To explore the role of accommodation environments in first year student mental health and wellbeing, eight focus groups were conducted in two universities in North West England and analysed using thematic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Our findings suggest that environment during isolation is a significant contributor to wellbeing, with those isolating with others seeming to fare better. Similarly, Worsley et al found that student accommodation offers the opportunity to cultivate a sense of community, with accommodation-based pastoral staff providing an important source of support for general student wellbeing and mental health concerns [35]. This echoes our finding that for some, isolation fostered a sense of community with others who were also isolating.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggest that environment during isolation is a significant contributor to wellbeing, with those isolating with others seeming to fare better. Similarly, Worsley et al found that student accommodation offers the opportunity to cultivate a sense of community, with accommodation-based pastoral staff providing an important source of support for general student wellbeing and mental health concerns [35]. This echoes our finding that for some, isolation fostered a sense of community with others who were also isolating.…”
Section: Discussionsupporting
confidence: 82%
“…For example, there is strong evidence of relationships between mental health problems and financial stress, 30,31 drug and alcohol consumption, 32,33 isolation and loneliness, 34 and sleep disruption 35,36 among students, as well as experiences of adverse events before and during university. 37 Although studies have increasingly explored the link between factors such as accommodation environments, 38,39 and physical activity 40 and student mental health, investigating general and comparative risk, protective and causal factors associated with mental health problems among students remains a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…The final score for the three subscales was obtained by multiplying the sum of the subscale scores by two. The depression levels of respondents are categorized as normal (0-9), mild (10-13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21-27), and extremely severe (≥28); anxiety levels are classified as normal (0-7), mild (8-9), moderate (10-14), severe (15)(16)(17)(18)(19), and extremely severe (≥20); and stress is broken down as normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26-33), and extremely severe (≥34). [14][15][16] Statistical Analysis: All the collected data were analysed using the IBM Statistical Package of Social Sciences (SPSS) version 16.0 software.…”
Section: Study Instrumentmentioning
confidence: 99%